Genomic characterization of the T-cell receptor loci in Ambystoma mexicanum - Pacheco-Olvera, Diana L.; Saint Remy-Hernández, Stephanie; Godoy-Lozano, E. Ernestina; Téllez-Sosa, Juan; Valdovinos-Torres, Humberto; Curiel-Quesada, Everado; López-Macías, Constantino; Martínez-Barnetche, Jesus (Frontiers in Immunology, 2025)
BackgroundAmphibians are valuable models for comparative immunology. In the caudate Ambystoma mexicanum, the architecture of immunoglobulin loci resembles that of the anuran Xenopus tropicalis, although some antibody gene features are absent. Evidence supports the presence of T lymphocytes in axolotl, the expression of T cell receptor alpha, beta, and delta chains, and a restricted diversity in the delta chain. Here, we describe the T cell receptor loci in the A. mexicanum genome and compare them with X. tropicalis and other tetrapods.MethodsT cell receptor loci were mapped and annotated in the A. mexicanum genome (UKY_AMEXF1_1) using reference sequences from axolotl, X. tropicalis, human, and mouse. Gene models were refined with RNA sequencing data from spleen, lung, and liver.ResultsThe T cell receptor alpha and delta locus in axolotl shows an overall conserved structure compared with other tetrapods. The alpha locus contained a higher number of variable genes than the beta and delta loci, with a predominance of functional genes (ratio 3.06). No gene encoding the pre-T cell receptor chain alpha was identified. The delta locus harbored two conventional variable genes, but no expression was detected in RNA sequencing data, suggesting pseudogenization. Neither delta chain diversity genes nor gamma chain elements were found in the genome or spleen transcriptome. The beta locus displayed structural similarity to that of other tetrapods and included five translocons with diversity, joining, and constant segments. One constant gene consisted of two exons encoding two constant domains. Functional variable genes predominated in the beta locus (ratio 3.6).ConclusionOur study reveals conserved but distinctive features of axolotl T cell receptor loci, including restricted delta-chain diversity, absence of gamma chain and pre-T cell receptor alpha, and structural novelty in the beta locus. These findings provide new insights into the evolution of T cell receptors in amphibians and offer a genomic framework to explore the links between adaptive immunity and tissue regeneration in A. mexicanum.